2004
DOI: 10.1590/s1516-89132004000500005
|View full text |Cite
|
Sign up to set email alerts
|

Initial segmentation patterns of microspores and pollen viability in soybean cultured anthers: indication of chromosome doubling

Abstract: Anthers obtained from flowers buds of soybean cultivar IAS -5 were cultured in two basal culture media (B5 and B5 long). Cytological examinations of the in vitro anthers were performed during the first 20 days of culture to assay the viability (by propionic-carmine and fluorescein diacetate tests) and the stage of development of pollen grains. The frequencies of viable pollen grains varied significantly between bud sizes on the propionic-carmine analysis.The basal culture media and bud size had no clear effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
1
6
0
2
Order By: Relevance
“…For multinucleate/multicellular structures, the means were 0.0125 for agarose and 0.0137 for Phytagel TM . Similar frequencies were reported for cultivar IAS-5 in previous studies (KaltchukSantos et al, 1997;Cardoso et al, 2004). Thus, results indicated that gelling agents had no influence on the segmentation pattern of microspores.…”
Section: Frequency Of Binucleate Pollen Grains and Multinucleate Strusupporting
confidence: 90%
“…For multinucleate/multicellular structures, the means were 0.0125 for agarose and 0.0137 for Phytagel TM . Similar frequencies were reported for cultivar IAS-5 in previous studies (KaltchukSantos et al, 1997;Cardoso et al, 2004). Thus, results indicated that gelling agents had no influence on the segmentation pattern of microspores.…”
Section: Frequency Of Binucleate Pollen Grains and Multinucleate Strusupporting
confidence: 90%
“…However, some advances have been achieved in alfalfa (Zagorska et al, 1997), Lupinus spp. (Bayliss et al, 2004;Ormerod & Caligari, 1994) and soybean (Cardoso et al, 2004;Rodrigues et al, 2005). The importance of this approach for plant breeding in Europe, has led to the COST action 851 "Gametic Cells and Molecular Breeding for Crop Improvement" (http://www.scri.sari.ac.uk/assoc/cost851) led by Brian P. Forster (Scottish Crop Research Institute) which includes some legumes.…”
Section: Double Haploids and Wide Hybridizationmentioning
confidence: 99%
“…Relatively poor progress has been achieved on androgenetic techniques in legumes (Croser et al 2006). Several attempts have been made to develop anther and microspore culture systems for soybean (Glycine max L.) (Cardoso et al 2004;Rodrigues et al 2004;Lauxen et al 2003;Kaltchuk-Santos et al 1997;Ye et al 1994), chickpea (Cicer arietinum L.) (Vessal et al 2002;Huda et al 2001;Bajaj and Gosal 1987;Khan and Ghosh 1983), alfalfa (Medicago sativa L.) (Zagorska and Dimitrov 1995;Tanner et al 1990), pigeonpea (Cajanus cajan L.) (Kaur and Bhalla 1998), Phaseolus vulgaris (Muñoz-Florez and Baudoin 1994a, b;Peters et al 1977). Few reports have been published on androgenesis induction in lupin (Lupinus L.) (Bayliss et al 2004;Ormerod and Caligari 1994;Sator et al 1983;Sator 1985).…”
Section: Introductionmentioning
confidence: 99%